Knowledge management and innovation in healthcare - N. N. Masyuk; O. M. Kulikova; E. V. Usacheva; N. S. Veremchuk (E-Management, 2024)
In order to increase the effectiveness of medical care and adapt to Industry 4.0 technologies, it becomes necessary to determine the current directions of healthcare development. The study purpose is to identify trends and development patterns of innovative technologies in the field of healthcare using data mining methods. The research methodology is based on the methods’ application of information messages’ text analysis. The data set was formed by parsing publications from Google RSS feeds and PubMed database for the period 2018–2022. To analyze the generated data sets, a dynamic modification of the BERTopic natural language processing model and the Bibliometrix library were used. To assess the differences in the structure of publications in the annual section, the Wilcoxon T-test was applied. The data sets contain 10,307 informational messages from leading publishers and 4,673 scientific publications. Four most relevant areas of research for the healthcare sector have been identified: 1) adaptive management in the field of healthcare; 2) information technologies in healthcare; 3) resource provision of medical organizations; 4) medical care for diseases. The most actively developing direction is related to the use of information technology. The number of publications on this issue in 2022 increased by 137.42% compared to 2020. The main areas of research are the development of medical CRM systems, the use of information technologies both for the development of tools for combating pandemics, and for methods of quality management and lean manufacturing. The study results can be used to improve the quality of medical care to the population of Russia.